Wonder feminisms: comics-based artivism against gender violence in Italy, intersectionality and transnationalism - Mandolini, Nicoletta (2022)
Since the beginning of the new millennium, the denunciation of gender-based violence has become widespread in Italy. Capitalising on the groundbreaking work of feminist movements of the 1970s and 1980s, a significant number of contemporary Italian collectives and networks have succeeded in bringing to the attention of mainstream media the issues of femicide, domestic abuse, rape and denied reproductive rights. Artivistic practices have played a crucial role in this process of mainstreaming. This article examines four comics-related artivistic experiences and it will do that by means of a hybrid methodology that brings together the social sciences method of the semi-structured interview with artists and activists and the Cultural Studies/Social Semiotics practice of textual/visual analysis. The adoption of these two approaches allows to gather insights both on the dynamics that regulate the ideation, realisation and promotion of the artivistic campaigns and on the results of the same artivistic practices, which is to say on the cultural products and their potential impact. These two areas are considered as interdependent, as demonstrated by the results of the study, which suggest that a deeper involvement of artivists with transnational intersectional feminist movements generally corresponds to a more inclusive, effective and participative artivistic product.